The method of finite spheres in acoustic wave propagation through nonhomogeneous media: Inf-sup stability conditions - Nicomedes, Williams L.; Bathe, Klaus-Jürgen; Moreira, Fernando J. S.; Mesquita, Renato C. (Vietnam Journal of Mechanics, 2020)
When the method of finite spheres is used for the solution of time-harmonic acoustic wave propagation problems in nonhomogeneous media, a mixed (or saddle-point) formulation is obtained in which the unknowns are the pressure fields and the Lagrange multiplier fields defined at the interfaces between the regions with distinct material properties. Then certain inf-sup conditions must be satisfied by the discretized spaces in order for the finite-dimensional problems to be well-posed. We discuss in this paper the analysis and use of these conditions. Since the conditions involve norms of functionals in fractional Sobolev spaces, we derive ‘stronger’ conditions that are simpler in form. These new conditions pave the way for the inf-sup testing, a tool for assessing the stability of the discretized problems.